PERANCANGAN SISTEM INFORMASI MANAJEMEN KEPEGAWAIAN BAGI UKM BERBASIS DIGITAL - Astitiani, Ni Luh Putu Surya; Widnyani, Ni Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.05.TAHUN.2022DO - 10.24843/EEB.2022.v11.i05.p02, 2022)
Currently information technology plays a role in solving a problem in order to increase the effectiveness and efficiency of work in a business company. Not only that, information technology can also simplify and speed up a business process within a company. SMEs can now take advantage of information technology for business management. One of the technologies that can be utilized by SMEs is a digital-based personnel management information system. The success of a business is highly dependent on good management, especially the management of human resources or employees. So far, there are still many SME entrepreneurs who have not carried out staffing management in a systematic manner, especially utilizing information technology. Realizing the situation and conditions mentioned above, it is necessary to have a digital-based personnel information system for SME entrepreneurs. In this research, a digital-based personnel management information system will be designed for SMEs. This system is expected to be able to assist and facilitate SME entrepreneurs in managing data and assessing employee performance, so that with this system decision making is faster and easier to do.